Barriers to Listening Comprehension in EFL Contexts: Evidence from Islamic University in Palembang - Muhammad Arif AlDaffa; Amalia Hasanah; Deta Desvitasari (Universitas Muhammadiyah Tangerang, 2026)
This research aims to identify problems faced by third-semester EFL students in the English Education study program at UIN Raden Fatah Palembang in learning listening comprehension during the 2023/2024 academic year. Using a qualitative case study approach, 8 students were selected through purposeful sampling technique, specifically homogenous sampling. Data were collected through semi-structured interviews to explore students’ experiences and perceptions in depth. The findings revealed several factors contributing to students’ problems in listening comprehension, including (1) different accent of speakers; (2) unclear pronunciation; (3) the length and speed of the listening; (4) the poor recording quality; and (5) background noise or distractions. This research highlights the importance of providing diverse and clear listening materials, using high quality audio devices, and ensuring a conducive classroom environment. As it focuses solely on students’ perspectives, further studies are recommended to investigate solutions and instructional strategies to address these listening comprehension problems effectively.